Variation of structural and hyperfine parameters of (Fe0.70Al0.30) 1-xNbx , with x=0, 0.05, 0.10 and 0.20 System (2020)
Fe0.70Al0.30 alloy is a bcc and ferromagnetic phase, being the Al atoms magnetic dilutor. In this work, we study the effect of the Nb on the structural and hyperfine behavior of the Fe0.70Al0.30 alloy when atoms of Nb substitute atoms of Fe or Al. The nanostructured system of (Fe0.70Al0.30)1-xNbx (x = 0, 0.05, 0.10, 0.20, at. %) was obtained by alloying Fe, Al and Nb powders in a planetary ball mill during 12 h, 24 h and 36 h, and a ball mass to powder mass relation of 10:1. The magnetic and hyperfine properties of the samples were studied by X-ray diffraction (XRD) and Mössbauer Spectrometry (MS) at room temperature, respectively. The X-ray diffraction patterns for x=0 showed the bcc-α FeAl structure and its lattice parameter is approximately constant with milling times (∼ 2.91 Å). For x=0.05, 0.10 and 0.20 the patterns showed the coexistence of the α-FeAl, Nb(Fe,Al)2 structural phases with an amorphous component. The Mössbauer spectra of x=0 samples were fitted using hyperfine magnetic field distributions (HMFDs), and the obtained mean hyperfine fields (MHF) were 23.4, 24.2, and 24.3 T for 12, 24, and 36 h of milling time, respectively, which correspond to the α-FeAl structure. The spectra of the samples with x=0.05 and 0.10 were fitted using a model with two components, the first one is a HMFD attributed to the bcc-FeAlNb structure and the second with two doublets attributed to the Nb(Fe,Al)2 structure. When atomic percentage of Nb increases up to 20 at. % the ferromagnetic behavior is diluted due to substitution of Fe-atoms by Nb and Al atoms in the bcc-FeAlNb structure. The magnetic behavior becomes paramagnetic at x=0.20, the spectra were fitted with three doublets, one of them related with bcc-FeAlNb structure and the others to the Nb(Fe,Al)2 structural phase. The alloying of Nb to the Fe0.70Al0.30 system destroyed the magnetism due the substitution of Fe by Nb atoms and generates an amorphization into the system